PENGARUH TEKNOLOGI TERHADAP PEMBENTUKAN ISTILAH BARU DALAM BAHASA ARAB - . Musthofa (Thaqafiyyat : Jurnal Bahasa, Peradaban dan Informasi Islam, 2013)
This paper will describes that Arabic language is one of the world languages that can grow and develop in response to scientific and technological development. In many cases, the growth and development of language can take in part the form of creation of new words. The growth and development of Arabic language, especially inthe form of creation of new words, are heavily influenced by technology, that is because all technologies influences on language, in ways that are not always obvious. In studying language and technology, we will look at how the technology influences on the language use. So when a completely new technology is pased to us, we feel like tryingto learn a new language with it's own syntax and vocabulary. For this reason, we can say that the emerging new technology has its impact on language. In fact, we can easily get new words in dictionaries, for example the new words ة (airplane), ر (train), درا(bicyle), ا (tank), ا (telephone), ا (telegram), (computer), (network, internet), and ة ا (window, for computer) that all of these are old vocabularywith new meaning. So we can get the new words ن !"#$% ا (televizion), ن #$% ا (telephone),اف '$% ا (telegraph), ا (torpedo), ب )$% ا (telescope), * (technic), +, أو(automatic), / آ (computer), and 12%23 ا (internet) that all of these are new vocabulary. These new Arabic words are created because of technology impact on Arabic. Some of these words are borrowed from English, and some other, are translated from English into Arabic. So we san say that "all technology has a connection to language use, and all technology influences language”.Keywords: language, Arabic, technology, development, influence, creation, and new words